Distribution patterns, habitat characteristics and population estimates of irrawaddy dolphins (Orcaella brevirostris) in Kuching Bay, Sarawak - Peter, Cindy (Universiti Malaysia Sarawak (UNIMAS), 2012)
Irrawaddy dolphin (Orcaella brevirostris) are known to be riverine and coastal dwelling animals which place them under pressure from human activities like fishing, coastal development and environmental pollution. Previously, there was a lack of baseline information on the population of Irrawaddy dolphins that are present in Kuching Bay. This lack of data impeded conservation and management efforts, as no one could determine how many dolphins there are, how are there distributed on a fine scale, or what their preferred habitat characteristics are.